Desenvolvimento de suporte para placa de revestimento cerâmico com incorporação do resíduo solido do tratamento de salmoura - Carnaúba, Tânia Maria Gomes Voronkoff (2018)
Industry sector is of great importance for economic development in every country. However, increasing discussions about environmental impacts led to strategies to minimize its effects, optimize production and technology, in a search for a process capable of superior production and lesser impact on nature. This thesis proposes development and analysis of supports for production of ceramic plates of a semi-porous kind (BIIb class), with water absorption between 6 -10%, and porcelain plates, with water absorption smaller than 0.5%. Inside the supports, we incorporated solid residues from the primary treatment of brine to be electrolyzed for production of caustic soda, hydrogen, and chlorine, using dry technology. The study was conducted from a partnership between industries from thermoplastic resin and ceramic plates production. Nowadays, Solid Residue from Brine Treatment (SRBT) is reinjected in salt mines which, although environmentally adequate, might not be the best solution. Therefore, we believe that SRBT incorporation at ceramic plate´s support is a viable alternative for better destination of this chemical residue that allows lower consumption of nature´s non-renewable resources and brings advantages to the support. This study generated 954 test subjects to verify the influence of different temperatures and SRBT concentrations in processing and densification using different tests. We test apparent density, linear retraction, water absorption, flexure strength, extraction expansion, black-heart formation, humidity expansion, thermal dilation coefficient and water loss in high temperatures. After the subject characterization, we gather that SRBT did not alter the main features of the material before burning, as presented by apparent density and mechanical strength tests. In all tested concentrations, rejects brought specific gains to mechanical strength especially for subjects of BIIb class. We infer that SRBT application in ceramic plates support is viable if one takes cautionary measures regarding homogenization of the material.